The evolution of PRRT for the treatment of neuroendocrine tumors; What comes next? - Harris, Philip E.; Zhernosekov, Konstantin (Frontiers in Endocrinology, 2022)
Lu-177 has been developed for the treatment of patients with peptide receptor radionuclide therapy (PRRT). A second generation pure no-carrier-added Lu-177 has a high specific activity and has waste disposal advantages over the first generation carrier-added Lu-177. PRRT has recently been developed for the treatment of neuroendocrine tumors (NETs). The majority of pancreatic and gastroenteric NETs (GEP-NETs) express the somatostatin receptors (SSTRs) 2 and 5. These receptors can be specifically targeted with a somatostatin peptide analogue (DOTATOC/DOTATATE) which can be chelated to a positron emission tomography (PET) emitting radioisotope such as Ga-68 for imaging or to a β-emitting radioisotope Lu-177 for therapy. A key advantage of this approach is that the receptor expression can be demonstrated by PET imaging before the patient is treated. Clinical studies in G1 and G2 GEP-NETS have demonstrated that PRRT is extremely effective in terms of progression free survival (PFS), symptom control and quality of life, with a well-established safety profile. A beneficial effect on outcome survival awaits to be confirmed. The first commercially available product Lu-177-DOTATATE was approved following the NETTER-1 trial in G1 and G2 GE-NETS. Lu-177-DOTATATE 7,4 GBq every 8 weeks for 4 cycles, together with octreotide LAR 30 mg monthly, demonstrated a median PFS of 28,4 months compared to 8,5 months for octreotide LAR 60 mg monthly. A second pivotal study COMPETE is currently in progress, comparing no carrier-added (n.c.a.) Lu-177-DOTATOC to the m-TOR inhibitor Everolimus in both GE-NETs and PNETs. Two studies, NETTER-2 and COMPOSE are currently underway in patients with high grade G2 and G3 NETs. Novel SSTR antagonists are being developed as next generation targeting molecules for SSTR2-expressing tumors. Antagonists have a higher tumor binding to receptors than agonists, opening up the potential indications for SSTR2 targeting to tumors which have a relatively lower expression of SSTR2 compared to NET such as small cell lung cancer, hepatocellular carcinoma and breast cancer.. In addition to Lu-177, radioisotopes with different radiation properties such as Tb-161 and the α-emitter Ac-225 are being developed which have the potential to improve treatment efficacy across the range of G1 to G3 NETs.